Análise econômica das compensações financeiras pagas por transgressões do limite dos indicadores de continuidade na distribuição de energia elétrica: o caso Celg (2014 a 2016) - Barbosa, Lucas Martins (2018)
The mechanisms for stimulating quality improvement in the provision of the electricity distribution service emerged along the evolution of the regulatory process in the Brazilian electric power sector, with emphasis on: the continuity indicators and the consequences of the poor quality of the services rendered the payment of financial compensation to consumers and the risk of loss of the concession right. From this history, the National Electric Energy Agency - ANEEL, under constant supervision pointed to Celg as one company that had one of the worst rankings in the continuity rankings, and one of the most paid financial compensation to its consumer units. This research investigates the reduction of the volume paid in financial compensation by Celg, about R$ 220 million (reais), between 2014 and 2016. This partnership had a set of information with more over 200 million observations of long-term interruptions in the distribution of electricity and payment of financial compensation. For this analysis, an investigation made of the roots of the current problem of poor quality of service rendering, noting that one of the main factors causing the current scenario is several failures in the regulatory process that occurred throughout the development of the Brazilian electricity sector and, also, the non-investment in periods of technological transition and expansion of the use of electric energy, which Celg is inserted. To mitigate the high amounts paid in financial compensation, two different analyzes carried out in two articles; the first under the method of quantum regressions and the second through an exploratory analysis of spatial data. These analyzes decide two investment policies carried out by Celg, one for the regions where they most paid financial compensation and another for which there was practically no violation of the limits of the continuity indicators. The first proposal is to start corrective investments, improving distribution systems with implementing automation devices of the system (re-closers), while the second proposal is based in the investment in the revision of the systems that paid few compensations, with the aim of avoiding future problems.